Aquatic microbiology and ecological approach - Edgcumbe Ford, Timothy (Estados Unidos | ESTADOS UNIDOS Blackwell Scientific Publications / Boston, 1993)
Contents: A prerspective on the ecology of aquatic microbes; The advances and limitation of methodology; Distribution and activity of microorganism in lakes effects of physical processess; Microbial biogeochemical activities in lakes; Stratification and eutrophication; The pelagic microbial food web of oligotrophic lakes
Sin Especificar
Keywords: Microbiología acuática | Ecología acuática